The rise and fall of the phlogiston theory: a tool to explain the use of models in science education - Mamlok-Naaman Rachel (Chemistry Teacher International, 2023)
The phlogiston theory was established around 1700 and lasted for about one hundred years. According to the Phlogiston Theory, phlogiston is released during heating processes, and the remaining material becomes lighter. The demise of this theory started with Lavoisier’s new insights into the phenomena of chemical reactions in general and combustion in particular, as well as about the composition of air. The rise and fall of the Phlogiston theory is a good example to the process of the replacement of one theory by another, due to new facts and new discoveries. In addition, it stresses the advantages and limitations of scientific models and theories, as well as the nature of science. A brief program, planned for two lessons, was developed around the Phlogiston Theory, in the framework of teaching and learning the “Science: An Ever-Developing Entity” program. Semi-structured interviews with teachers and students were conducted after the completion of the Phlogiston topic. Based on the findings, it is suggested that the brief program, reached its goals. The students, who studied the program, learned more about the scientists – their curiosity and their boldness, as well as about the scientific endeavor, consisting of discoveries, models and theories.